Let Your Lawn Tell You When To Water - Laurie E. Trenholm; J. Bryan Unruh (EDIS)
Revised! ENH-63, a 3-page illustrated fact sheet by L.E. Trenholm and J. Bryan Unruh, helps homeowners avoid overwatering their lawns by operating irrigation systems only when the lawn shows signs of drought stress. Published by the UF Department of Environmental Horticulture, November 2008.